GRAZING BEHAVIOR OF AFRICANIZED HONEY BEES (Apis mellifera L.) IN FLOWERS OF YELLOW MELON (Cucumis melo L.)o L.) - Sousa, Raimundo Maciel de; Aguiar, Odaci de Sousa; Freitas, Breno Magalhães; Maracajá, Patrício Borges; Andrade, Carlos Benhu Caetano Maia de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
Africanized bee colonies (Apis mellifera L.) were introduced in areas of commercial cultivation of yellow melon (Cucumis melo L.), in Acaraú-CE, Brazil. It was observed the following aspects of the grazing activity of bees in the flowers of culture: frequency of bees during the day, the type of food collected, the time spent per visit, culture and constancy in the number of visits received per flower. The frequency of bees in the flowers of melon showed statistically significant differences (P <0.05) between the hours of observation, concentrating their visits between 05:00 h and 07:00 h. The frequency of bees returning to the hives showed significant differences (P <0.05), with higher activity between 05:00 h and 07:00 h. The number of pollen foragers returning the hives was higher in the schedule of 05:00 h differed significantly (P <0.05) from other times. The time spent per visit (n = 200 flowers) ranged from 2.0 to 34.3 seconds, averaging 13.18 ± 9.29 seconds. Time to collect pollen was significantly higher (P <0.05), with a mean of 21.3 ± 6.1 seconds. It was concluded that honeybees have a higher frequency in the flowers of melon during the early morning hours, with marked preference for pollen collection.